Using the FroggyBobby exergame to support eye-body coordination development of children with severe autism. Issue 105 (September 2017) - Caro, Karina; Tentori, Mónica; Martinez-Garcia, Ana I.; Alvelais, Marina
Abstract: Children with severe autism lack of the eye-body coordination skills which are needed to conduct aimed limb movements. Physical therapy relies on the repetition of limb movements that demands children with severe autism to aim for a visual target. But their movements during physical therapies are most of the time aimless, and they found the visual stimuli confusing and not engaging. Exergames could support motor therapies as they combine game technology with exercise activity. This technology can offer a natural interaction and use multisensory stimuli appropriate to keep children with autism focused during motor therapeutic interventions. In this paper, we hypothesize that exergames supporting motor therapeutic interventions and alleviating such attention and motor challenges could help children with severe autism to develop the necessary coordination skills needed to follow up visual targets. We present a 7-weeks evaluation study of the deployment of an exergame supporting the practice of eye-body coordination exercises. Seven children with severe autism and three psychotherapists participated in the study. Our results indicate children with severe autism maintained their attention for the total duration of the therapy, reduced their aimless limb movements and developed aimed limb movements, as a result of weeks of usage of the exergame. We close discussing challenges for existing clinical practice from a design and clinical point of view.